Immune cell status, cardiorespiratory fitness and body composition among breast cancer survivors and healthy women: a cross sectional study - Arana Echarri, Ainhoa; Struszczak, Lauren; Beresford, Mark; Campbell, John P.; Jones, Robert H.; Thompson, Dylan; Turner, James E. (Frontiers in Physiology, 2023)
Methods: We examined whether immune cell profiles differ between healthy women (n = 38) and breast cancer survivors (n = 27) within 2 years of treatment, and whether any group-differences were influenced by age, cytomegalovirus infection, cardiorespiratory fitness and body composition. Using flow cytometry, CD4+ and CD8+ T cell subsets, including naïve (NA), central memory (CM) and effector cells (EM and EMRA) were identified using CD27/CD45RA. Activation was measured by HLA-DR expression. Stem cell-like memory T cells (TSCMs) were identified using CD95/CD127. B cells, including plasmablasts, memory, immature and naïve cells were identified using CD19/CD27/CD38/CD10. Effector and regulatory Natural Killer cells were identified using CD56/CD16. Results: Compared to healthy women, CD4+ CM were +Δ21% higher among survivors (p = 0.028) and CD8+ NA were −Δ25% lower (p = 0.034). Across CD4+ and CD8+ subsets, the proportion of activated (HLA-DR+) cells was +Δ31% higher among survivors: CD4+ CM (+Δ25%), CD4+ EM (+Δ32%) and CD4+ EMRA (+Δ43%), total CD8+ (+Δ30%), CD8+ EM (+Δ30%) and CD8+ EMRA (+Δ25%) (p < 0.046). The counts of immature B cells, NK cells and CD16+ NK effector cells were higher among survivors (+Δ100%, +Δ108% and +Δ143% respectively, p < 0.04). Subsequent analyses examined whether statistically significant differences in participant characteristics, influenced immunological differences between groups. Compared to healthy women, survivors were older (56 ± 6 y vs. 45 ± 11 y), had lower cardiorespiratory fitness (V̇O2max mL kg−1 min−1: 28.8 ± 5.0 vs. 36.2 ± 8.5), lower lean mass (42.3 ± 5.0 kg vs. 48.4 ± 15.8 kg), higher body fat (36.3% ± 5.3% vs. 32.7% ± 6.4%) and higher fat mass index (FMI kg/m2: 9.5 ± 2.2 vs. 8.1 ± 2.7) (all p < 0.033). Analysis of covariance revealed divergent moderating effects of age, CMV serostatus, cardiorespiratory fitness and body composition on the differences in immune cell profiles between groups, depending on the cell type examined. Moreover, across all participants, fat mass index was positively associated with the proportion of HLA-DR+ CD4+ EMRA and CD8+ EM/EMRA T cells (Pearson correlation: r > 0.305, p < 0.019). The association between fat mass index and HLA-DR+ CD8+ EMRA T cells withstood statistical adjustment for all variables, including age, CMV serostatus, lean mass and cardiorespiratory fitness, potentially implicating these cells as contributors to inflammatory/immune-dysfunction in overweight/obesity.